Analisis Analisis Kebangkrutan dengan Model Altman Z-score pada PT Bank Panin Dubai Syariah Tbk tahun 2016-2019 - Rokhmah Mutakhidah; Yacobo P. Sijabat (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2020)
The aims of study is to determine whether there is still a potential bankruptcy at PT Bank Panin Dubai Syariah Tbk from 2016-2019. This study used the model of Altman Z-Modified Model. The analyze is by looking at financial statements and financial ratios. The sample used in this study was PT. Bank Panin Dubai Syariah Tbk. Year 2016-2019. The results of the study stated that PT Bank Panin Dubai Syariah Tbk is far from potential bankruptcy with the Z-Score being above the threshold. But there are still not optimal in the financial statements such as retained earnings and profits generated by PT Bank Panin Dubai Syariah Tbk.Keywords: Bankruptcy, Financial statements, Altman Z-Score Modified Model